Cloud-Based Execution to Improve Mobile Application Energy Efficiency. - Tilevich, Eli; Young-Woo Kwon (Computer (00189162), 2014)
Cloud offloading--a popular energy optimization technique--executes a mobile application's energy-intensive functionality via a cloud-based server. To maximize efficiency, systems must determine the functionality to offload at runtime, which will require innovation in both automated program transformation and systematic runtime adaptation.